Factors affecting satisfaction with education program for chronic airway disease in primary care settings - Kim, Andrew; Hwang, Yong Il; Kim, Joo Hee; Jang, Seung Hun; Park, Sunghoon; Park, Ji Young; Jung, Ki-Suck; Yoo, Kwang Ha; Park, Yong Bum; Yoon, Hyoung Kyu; Rhee, Chin Kook; Kim, Deog Kyeom; et al. (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Background: A well-organized education program improved the patients’ knowledge about their disease, inhaler technique and quality of life in asthma and chronic obstructive pulmonary disease (COPD) patients. The effectiveness of the education program can be evaluated by assessing patients’ satisfaction with the education program as well. In this study, we compared the patients’ satisfaction with education program between COPD and asthma patients. Methods: A total of 284 asthma and COPD patients were enrolled. Three educational visits were conducted at 2-week intervals. On the first visit, we taught the patients about their diseases and the proper inhaler technique. On the second visit, non-pharmacologic treatments and action plans for acute exacerbation were introduced. On the final appointment, we summarized the educational concepts covered in the two prior visits. After the education program, the patients were assessed for their quality of life, knowledge of chronic airways disease, and satisfaction with the education program, using a structured questionnaire. Results: After the education program, 99.3% of the asthma patients knew much more about their disease and 96.8% agreed that education from the hospital is needed. For COPD patients, 94.8% felt more informed about their disease and 95.7% agreed that education from the hospital is needed. However, 17.1% of asthma patients and 13.5% of COPD patients disagreed to paying an additional fee for the education program. Finally, the knowledge improvement was linked to patient satisfaction with the education program. Conclusions: The improvement in self-knowledge about their disease was linked to their satisfaction with the education program. However, costs associated with the program could limit its accessibility to the patients. The patient education program is a self-management intervention to improve the lives of patients with asthma and COPD. Thus, a policy to reduce the economic burden of the patients should be considered to disseminate the education program in primary care clinics.